Determinants of Multidisciplinary Team Knowledge about Case Managers: A Quantitative Study - Ni Luh Putu Lusiana Devi; Ni Nyoman Ari Kundari Dewi (Indonesian Journal of Global Health Research, 2025)
The implementation of the case manager (CM) has not been optimal according to what was expected. Even though there is a positive perception about the role of CM held by nurses and NA as part of the Professional Care Providers (PPA) is very necessary. The knowledge factor is the factor that has the most influence on positive perceptions about the role of CM. There are many things that can influence nurses' and NAs' knowledge about CM. This study aims to determine the factors related to nurses' and NAs' knowledge about CM. This quantitative correlational research used a cross-sectional approach involving 384 nurses and 129 NAs. The sampling technique used is multistage random sampling and simple random sampling. Each respondent has filled out a structured questionnaire via Google Form and has been analyzed using descriptive statistics, chi-square test, and binary logistic regression. This study used a questionnaire on knowledge about CM with a Cronbach Alpha value of 0.634. This research found that the majority of nurses and NAs had insufficient knowledge about CM, 248 people (65%) and 80 people (62%). The factors age, education and length of service were associated with nurses' knowledge about CM (p=0.001; p<0.001; and p<0.001). The factors age and years of service were associated with NA's knowledge about CM (p=0.017; and p=0.024). This study also found that knowledge was a determining factor in nurses' knowledge about CM (OR=2.53; 95%CI 1.60-4.01; p<0.001). These findings support the theory that age, education and years of service are related to knowledge about CM. Socialization about case managers and increasing the role of case managers in services needs to be carried out by hospital management.